2002
DOI: 10.3201/eid0806.010370
|View full text |Cite
|
Sign up to set email alerts
|

Medical Care Capacity for Influenza Outbreaks, Los Angeles

Abstract: In December 1997, media reported hospital overcrowding and “the worst [flu epidemic] in the past two decades” in Los Angeles County (LAC). We found that rates of pneumonia and influenza deaths, hospitalizations, and claims were substantially higher for the 1997–98 influenza season than the previous six seasons. Hours of emergency medical services (EMS) diversion (when emergency departments could not receive incoming patients) peaked during the influenza seasons studied; the number of EMS diversion hours per se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 12 publications
(13 reference statements)
0
50
1
Order By: Relevance
“…15,16,20 However, unlike the wellcharacterized and familiar symptoms and cause of influenza, SARS emerged as a new infection caused by a poorly understood virus. Furthermore, its rapid local and international spread and its ability to infect large numbers of healthy hospital staff, 5,21 some of whom required intensive care, generated much attention in the global media.…”
Section: Discussionmentioning
confidence: 99%
“…15,16,20 However, unlike the wellcharacterized and familiar symptoms and cause of influenza, SARS emerged as a new infection caused by a poorly understood virus. Furthermore, its rapid local and international spread and its ability to infect large numbers of healthy hospital staff, 5,21 some of whom required intensive care, generated much attention in the global media.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemic peaks during the winter months are usually caused by influenza virus and respiratory syncytial virus (RSV), while other viruses such as human metapneumovirus (MPV) and parainfluenza viruses (PIVs) also circulate in fall and winter [2]. There is a corresponding winter increase in presentations to emergency departments and outpatient clinics [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The idea is that, apart from its own regular electrically-induced beating beats, the heart is also regulated by the ANS. For In the past twenty 20 years, many articles studies have indicated that there is the significant relationship between the ANS and mortality exists that are caused by results from cardiovascular diseases, for example such as sudden death [1] , hypertension [2], hemorrhagic shock [3], and septic shock [4][5][6], HRV predict mortality rates related to certain cardiovascular diseases, can be grouped into time and frequency domains, and is most commonly computed as a series of R-to-R peak interval (RRI) times through electrocardiography. HRV usually excludes arrhythmias and other markedly abnormal rhythmic diseases and targets minor heart rate variations with normal heart rhythm.…”
Section: Introductionmentioning
confidence: 99%